우지 Alcoholysis 반응물을 이용한 Oil-in-Water Emulsion의 포화도에 따른 산화특성 및 안정성 연구 - 장화(Hua Zhang); 이영화(Young-Hwa Lee); 신정아(Jung-Ah Shin); 이기택(Ki-Teak Lee); 홍순택(Soon-Teak Hong) (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2013)
In this study, methyl esters with different saturated fatty acids (SFA) were prepared by urea fractionation to make an oil-in-water emulsion. Emulsion characteristics (emulsion stability and oxidative stability) of the methyl ester emulsion were then studied at different percentages of methyl ester saturation (5, 28, 39, 50, and 72%, termed ${Σ}$SFA5, ${Σ}$SFA28, ${Σ}$SFA39, ${Σ}$SFA50, and ${Σ}$SFA72, respectively). The stability of emulsions (ES) with different SFA content was 46.0 (${Σ}$SFA5), 39.5 (${Σ}$SFA28), 32.7 (${Σ}$SFA39), 32.6 (${Σ}$SFA50), and 27.3 (${Σ}$SFA72). Results from Turbiscan showed that creaming or clarification, based on the backscattering intensity, was more pronounced with increases in the saturation degree of the emulsion. These results implied that the emulsions with lower saturation were more stable. During 30 days of storage, the lipid peroxide value increased for all emulsions, with the increase less pronounced with the increasing saturation of the emulsion; 1.880 (${Σ}$ SFA5), 1.267 (${Σ}$SFA28), 1.062 (${Σ}$SFA39), 0.342 (${Σ}$SFA50) and 0.153 (${Σ}$SFA72) mg $H_2O_2/mL$ emulsion. In addition, thiobarbituric acid reactive substances (TBARS) values were significantly lower in emulsions with high saturation (4.419 mg for ${Σ}$SFA50 and 4.226 mg for ${Σ}$SFA72) than emulsions with low saturation (6.229 mg for ${Σ}$SFA5, 6.801 mg for ${Σ}$SFA28 and 6.246 mg for ${Σ}$SFA39). In conclusion, the emulsions with a higher saturation degree of methyl esters showed lower emulsion stability but better oxidation stability. 본 연구는 urea fractionation을 통하여 포화도 함량이 5.8%, 28.4%, 39.2%, 50.7%, 72.3%인 우지 alcoholysis 반응물을 제조하고, 이를 유상(oil phase)으로 ultrasonic processor 및 고압균질기를 이용하여 emulsion을 제조한 후 이에 대한 유화 안정성과 산화 안정성을 실험하였다. 유화 안정성(ES)을 관찰한 결과 ES값은 46.0(${Σ}$SFA5), 39.5(${Σ}$SFA28), 32.7(${Σ}$SFA39), 32.6(${Σ}$SFA50) 및 27.3(${Σ}$SFA72)로써 포화도가 낮은 emulsion일수록 높은 안정성을 보였으며, Turbiscan을 이용하여 시료 emulsion의 creaming 및 clarification 특성을 조사한 결과도 ES 결과와 유사하게 나타났다. 고압균질기로 제조한 emulsion 시료에 대하여 30일간 산화특성 및 안정성 연구를 진행한 결과, 제조한 emulsion의 hydroperoxides 함량이 1.880(${Σ}$SFA5), 1.267(${Σ}$SFA28), 1.062(${Σ}$SFA39), 0.342(${Σ}$SFA50) 및 0.153(${Σ}$SFA72)mg $H_2O_2/mL$로 서로 유의적 차이(p<0.05)를 나타내면서 불포화도가 높은 emulsion 시료일수록 hydroperoxide의 함량이 높았고, TBARS 값은 저장 30일에 6.229(${Σ}$SFA5), 6.801(${Σ}$SFA28), 6.246(${Σ}$SFA39), 4.419(${Σ}$SFA50) 및 4.226(${Σ}$SFA72) mg TBA/mL로 ${Σ}$SFA50과 ${Σ}$SFA72가 다른 emulsion 시료보다 유의적으로(p<0.05) 낮은 값을 보이며 산화 안정성이 우수하였다.